STUDI AKTIVITAS ANTIDIABET CUKA BUAH MANGROVE PEDADA (Sonneratia alba) SECARA IN VIVO - Hardoko, Mr.; Sasmito, Bambang Budi; Fitriani, Eka Nurul (JFMR (Journal of Fisheries and Marine Research), 2020)
Antidiabetic activity of a substance can be studied in vitro using an enzyme or in vivo using rats. This research aimed to study the antidiabetic activity of mangrove fruit vinegar in reducing the blood glucose of diabetic white rats. The research method used was an experimental method with treatment of fruit vinegar dose (0.2; 0.4; 0.6 ml / rat / day, positive control, negative control) and duration of fruit vinegar administration (0, 7, 14 and 21 days) on diabetic white rat. Results showed that pedada fruit vinegar was able to reduce the blood glucose of diabetic rats. The ability of vinegar to reduce blood glucose on diabetic rats was influenced by the dose and duration of administration of fruit vinegar. The dose of vinegar administration on the diabetic rats which gave the similar results to the drug glibenclamide (positive control) was 0.4 ml / rat / day with a duration of administration of Â 14 days.